Disturbed forests, fragmented memories : Jarai and other lives in the Cambodian highlands - Padwe, Jonathan (Culture, place, and nature., 2020)
"This study of the cultural and ecological dimensions of waves of dispossession in Cambodia's northeast highlands focuses on the Jarai minority ethnic group. Presented from the perspective of the residents of Tang Kadon, a village of Jarai hill-rice farmers located just a few kilometers from the Vietnam border, it weaves together historical background on the often-racist perceptions of the Jarai by lowland Cambodians and Westerners with rich ethnography that presents living memories of how the residents of Tang Kadon survived aerial bombardment and a land invasion during the Vietnam War, only to find themselves relocated to the "killing fields" of the Khmer Rouge regime. Tracing the mutual influences of people on land and land on people, it narrates highlanders' successful efforts to put back together their complex, highly diverse agricultural system, seed by seed, after a decades-long interruption. By focusing on the relationship between processes of social change and human-environment relations, from the days of the precolonial slave trade to the present moment of land grabs along a rapidly transforming resource frontier, the book shows how history and memory are visible in the land. It addresses timely issues in anthropology and political ecology, and will be of interest to readers in allied fields including environmental studies, geography, and Southeast Asian studies"--